Lead poisoning in wildfowl - Olney, P J S (Wildfowl, 1960)
The symptoms and pathology of lead poisoning are fully described, with special reference being made to diagnostic features which could be used in any quantitative assessment. The amount of lead shot which constitutes a fatal dose is discussed. It is estimated that 60/80% of adult Mallard with one ingested pellet will succumb, if they are feeding on a diet of wild seeds. The availability of lead shot pellets to wildfowl on a particular body of water is determined by 1) the shooting intensity and number of shot deposited on the bottom, 2) the nature of the bottom material and 3) the size of the shot pellets involved. The incidence of ingested pellets can be determined by fluoroscopic examination and examination of viscera material, and will vary with the species and its feeding habits. Tables showing the incidence of ingested lead shot in four species of dabbling ducks in this country and in comparable species in North America are shown and discussed. There is a marked similarity between Mallard in this country and North America carrying ingested lead. The reproductive capacities of poisoned wildfowl do not seem to be seriously affected. The variations in mortality between different ages and sexes are attributed primarily to differences in the quality and quantity of food consumed. Means of reducing or eliminating losses are discussed, including the use of non-toxic shot, encouraging the growth of natural foods most likely to alleviate the poisoning effects, and more care in the choice of shot range. As yet no satisfactory non-toxic shot has been produced.